Independent Value of Cardiac Troponin T and Left Ventricular Global Longitudinal Strain in Predicting All-Cause Mortality among Stable Hemodialysis Patients with Preserved Left Ventricular Ejection Fraction. (7th May 2014) - Sung, Junne-Ming; Su, Chi-Ting; Chang, Yu-Tzu; Su, Yu-Ru; Tsai, Wei-Chuan; Wang, Saprina P. H.; Yang, Chun-Shin; Tsai, Liang-Miin; Chen, Jyh-Hong; Liu, Yen-Wen
Abstract : Using a speckle-tracking echocardiography (STE), we recently demonstrated that a left ventricular (LV) global longitudinal strain (GLS) ≥ −15% and the serum cardiac troponin T (cTnT) concentration are associated with mortality in stable hemodialysis patients with preserved LV ejection fraction (LVEF). In this study, we explored the relationship between cTnT and echocardiographic parameters and evaluated whether the prognostic value provided by cTnT is independent of a GLS ≥ −15% and vice versa. Eighty-eight stable hemodialysis patients with preserved LVEF were followed for 31 months. STE studies and measurements of cTnT were performed at baseline. CTnT concentration had a modest correlation with GLS (r s = 0.44 ; P < 0.001 ) but had a weak or nonsignificant correlation with other echocardiographic parameters. Adjusting for clinical parameters, hazard ratios for each increase of 0.01 ng/mL in cTnT, and a GLS ≥ −15% on mortality were 1.13 (P = 0.009 ) and 3.09 (P = 0.03 ) without significant interaction between cTnT and GLS ≥ −15%. In addition, an increased cTnT concentration, a GLS ≥ −15%, or their combination showed significant additional predictive value for mortality when included in models consisting of clinical parameters. Therefore, both cTnT and a GLS ≥ −15% are independent predictors of mortality and are useful for risk stratification.